Difference of structures of functional indicators in cyclic sports athletes - Shirkovets, E. A.; Morozov, V. N.; Rybina, I. L. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The analysis of the structures of functional indicator of qualified athletes. As the initial indicators for the factor analysis were chosen 14 parameters that characterize the performance in such cyclic sports as swimming, rowing, biathlon and cross-country skiing. The interrelation of anthropometric indicators, ergometric data at performance of the step test, heart rate at the last step of the test, informative metabolites of power supply, and also enzymatic and hematological indicators is studied. During the factor analysis by the principal components method, hidden common factors were identified, which allowedto reduce the dimension of the initial matrix of variables.